Sobre o anel de endomorfismos do módulo de cohomologia local - Gonçalves Junior, José (2016)
In this work, we study the first no-zero local cohomology module of a local Noetherian ring, its ring of endomorphisms and the ring of endomorphism of the dual of such module. We show sufficiency conditions in order to these rings being isomorphic.